The Effect of trans Ligands in the NO‐Linkage Reverse Isomerization for Ruthenium–Nitrosyl–Tetraammine Complexes: A DFT Study. Issue 23 (19th June 2017) - Yamaletdinov, Ruslan D.; Zilberberg, Igor L.
Abstract : The rearrangement of the NO ligand in ruthenium–nitrosyl–tetraammine complexes trans ‐[Ru(NO)(NH3 )4 X] 2+ (X = F –, Cl –, OH –, SH – ) has been studied for metastable oxygen‐coordinated NO complexes by means of DFT. On the basis of obtained data, this rearrangement is concluded to be caused by ligand‐to‐metal charge transfer of the p (X)→π*(Ru–ON) type. The excitation energy for electron transfer from p ‐orbital of ligand to LUMO correlates perfectly with the activation energy of isomerization. Found correlations are explained in terms of electronegativity of the trans ligand X. Abstract : A DFT study for the NO‐linkage isomerization in [Ru(NO)(NH3 )4 X] 2+ complexes reveals a linear correlation between the activation energy for the transition from an O‐bound metastable isomer to a sideways‐bonded isomer and the electron transfer energy from the trans ‐to‐NO ligand X to the antibonding orbital π*(Ru–ON). The higher the electronegativity of ligand X, the higher the barrier.